MINAT LULUSAN S1 PENDIDIKAN BAHASA ARAB PTKI LAMPUNG TERHADAP LANJUT STUDI S2 PBA PASCASARJAN - Khoirurrijal Khoirurrijal; abdul Mujib (Pascasarjana IAIN Metro, 2019)
Cost readiness is a picture of a good economic situation. The family's economic situation is closely related to children's learning. This, in line with the opinion of Slameto, states that children who are learning must meet their basic needs for learning facilities. The learning facilities can only be fulfilled if the family has enough money. That means, a person's economic situation will influence his choice of education to carry out further studies. Universities should observe income trends, personal savings, and banks as services to help finance education. This will affect the number of prospective students who will carry out further studies and can take steps to redesign, reposition, and reassign the work program quickly. Therefore, according to Slameto that the family economy is related to children who will study further, because learning facilities can only be fulfilled if the family has enough money. Language readiness is the second supporter besides cost readiness. Therefore, to enter Postgraduate, there are Arabic and English language test requirements, in addition to the TPA test and knowledge about the subject matter. This was stated in the SOP of the IAIN Metro Postgraduate New Student Registration. Support from parents or family is very important. This is according to Slameto's opinion that the Family is the first and foremost educational institution. Family that is very big means for education in small size, but it is to determine education in large measure, namely the education of the nation. Or in other words that the family can greatly influence the future study of prospective graduate students. The desire factor to improve knowledge and worship is one of the motivations for further study. This is according to Slameto's opinion, that motivation is a psychological factor in a person. Someone has needs at a time. There are biological needs, which arise from forced circumstances such as hunger, thirst, or feeling uncomfortable. Other needs are psychological, arising from the need to be recognized, valued, or belonging.